The mythopoetic modeling in prose of Olena Pechorna and Alla Rogashko (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
In this article the typological similarity and originality of the mythopoetical modeling in the prose by Olena Pechorna and Alla Rogashko are certain for the first time. The key in this context become such questions: the determination of the main facilities of creation of the mythopoetical atmosphere in the artistic works of the named authors and also the finding of the interpretation of these writers’ place in the modern to them system of the national woman prose.
Keywords: motive; model; concept; mythopoetics; bodycentrizm; suggestion; psychologism; typology